SUSTAINABLE MARKETING STRATEGIES ADOPTED BY WARANGAL DURRIE WEAVERS IN PRE & POST COVID-19 ERA - Aruna, K.; Kurisetti, Padma (The journal of contemporary issues in business and government, 2022)
The total world was affected by the COVID-19 pandemic from January 2020 onwards. Till today the impact of the pandemic is there and our Nation, India is coming back to new normalcy. Each and every sector of the economy, in India got affected by the pandemic. Various businesses had to undergo completely unexpected and challenging situations and required to formulate new strategies for their survival. Under such category majority of MSME’s, and labour force in unorganized sector, such as construction workers and artisans faced a challenging situation for their own sustainability. In India, un-organized sector got effected very badly. For example, handloom industry is one among them. Few selected industries, such as pharmaceutical, healthcare, online education, e-commerce and packaged consumer goods are benefited from the COVID-19 /pandemic and even the society got the benefit of additional employment with different skill sets. Unorganized sector like Handloom industry faced the challenging situation during the COVID-19. The artisans suffered a lot without work orders and sales. This study throws a light on the weavers of Warangal, who are famous for weaving durries. Their product is recognized with prestigious Geographical Indicator (GI). Main aim of this paper is to analyze the challenges of durrie weavers in pre and post pandemic period in India and to identify new strategies adopted by the weavers during the COVID-19 and suggest the marketing strategies to be adopted based on the results obtained from the study. This study includes two co-operative societies i.e., Shatranji & Nawar co-operative society and Kashivisheshwara co-operative society. The study used tools named as correlation analysis and Chi-Square test for analyzing the data.